POPULATION OF POLLINATING INSECTS (Elaeidobius kamerunicus Faust) ON OIL PALM PLANTS IN SIMALUNGUN REGENCY NORTH SUMATRA - Eka Bobby Febrianto; Chairul Maulana Nasution; M. Yusuf Dibisono; Gali Rakasiwi (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
The population of the oil palm pollinating beetle, Elaeidobius kamerunicus Faust, is an important biological indicator for assessing the adequacy of pollination and fruit set formation in oil palm plantations. This study aimed to measure the population and sex ratio of E. kamerunicus on male oil palm flowers in the anthesis phase from two planting years, namely 2013 and 2016. The study was conducted at PT. Perkebunan Nusantara IV Regional II, Afdeling VI, located in Dolok Batu Nanggar Subdistrict, Simalungun Regency, North Sumatra Province. The study took place from June to September 2023. It employed a survey method, and no experimental treatments were applied. Data analysis utilized descriptive statistics (mean and standard deviation) as well as Welch’s t-test to compare the two planting years. The results showed that the 2016 growing season had a slightly higher number of male inflorescences per observation plot, while the 2013 growing season had a significantly higher number of grains per panicle and a significantly higher estimated population of E. kamerunicus. The average population in the 2013 growing season reached 29,017.69 adult individuals ha?¹, whereas in the 2016 growing season, the average was 19,098.41 adult individuals ha?¹ and slightly below the commonly used minimum threshold of approximately 20,000 adult individuals ha?¹. The sex ratio was dominated by females in both growing seasons, with no significant difference between them.